Rabiscos na ponta do lápis: concepções de língua, linguagem, ensino e aprendizagem - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
This research is articulated with the Group of Reading, Research and Intervention in Reading, Writing and Literature in the School (LELIT), which, in turn, is connected to the line of re-search Educational Practices, Languages and Technologies / PPGE-UFOPA. Its general objective is to identify the conception of teaching and learning of reading and writing that emanates from the magazine Na ponta do lápis of the Olimpíada de Língua Portuguesa Escrevendo o Futuro – OLP, within the general framework that is drawn from the conception of reading writing teaching of the contemporary Brazilian education. Apparently, the OLP is only a text contest, but, in addition, it intends to offer teachers an opportunity for training, betting on the idea that teachers can experience a methodology of language teaching that works with textual genres through didactic sequences. Although the contribution of the OLP to the teaching of Portuguese Language is recognized, with the adoption of textual genres in its policy of teacher training, its pedagogical material and the production of text for the competition, this research investigated conceptual and underlying the proposal. The twenty-nine maganizes, produced from 2005 to 2017, were analyzed in their sections and classified in voices A, B, C and D according to the methodology adopted. Each section was examined considering the following categories: language; reading; teaching and learning; subject and authorship; teach-ing proposals and teacher; included in the guiding questions of the research. The overall study of the journals shows that the OLP (as voice A, official) intends to contribute to the formation of Portuguese-speaking teachers, from the conception that language has as interaction process, that is, users of the language or interlocutors interact as subjects who occupy social places and speak and hear of these places according to imaginary formations (images) that society estab-lishes, conceiving language as a living, flexible system that varies, that is, as a social phenomenon. In addition, the OLP is a program that has partners, intellectuals, artists and other teachers (other voices in existence), who seek to speak according to the voice of the institution, making us aware that the voices present in PL do not contradict the OLP, but maintains dia-logue with the conception of teaching and learning proposed by it and is concerned with the emancipation of the subjects involved in the whole process.
Keywords: Leitura; Escrita; Gêneros textuais; Ensino; Olimpíada de Língua Portuguesa; Língua Portuguesa; CNPQ:: CIÊNCIAS HUMANAS::EDUCAÇÃO::ENSINO SUPERIOR::LEITURA; PRÁTICAS EDUCATIVAS, LINGUAGENS E TECNOLOGIAS; Linguagem e Educação